Emergency medical team reclassification in WHO’s Western Pacific Region: continuous learning and improvement of health emergency response capacities - Casey, Sean T; Cosico, Roy; Salamanca, Jorge; Lajolo, Camila; Noste, Erin; Warren, Kathleen; Gilmore, Chandra; Grusd, Eystein; Larsen, Jan-Erik; Beauchemin, Pierre-Yves; Salio, Flavio (Western Pacific Surveillance and Response, 2025)
This manuscript details the process and outcomes of emergency medical team (EMT) reclassification in WHO’s Western Pacific Region. EMT reclassification is undertaken approximately 5 years after initial classification, ensuring adherence to published common EMT principles and standards. This report reflects on the first four EMTs reclassified in the Western Pacific Region, detailing the reclassification process and notable outcomes.
Keywords: emergency medical team; classification; health emergency; disaster; quality assurance; learning; improvement; health security